Effects of Nitrosamines on Hepatic Enzymes Activities and Histopathological Studies of White Mice (Mus Musculus) - Karruppan, Jeeven (2005)
Dietary and environmental hepatocarcinogens will be metabolized to active compounds and it must be detoxified in order to maintain liver integrity. In this study the feeding of nitrosamines and their effects on turnour marker enzymes Alkaline Phosphatase (ALP), Gamma-Glutamyl Transpeptidase (GGT), Glutathione S-transferase (GST) and Uridyl diphospho-glucuronosyl transferase (UDPGT) were analyzed in mice liver. The initial work involved homogenization of liver samples with different buffers at various concentrations. Results with ALP and GGT shows highest specific activities for liver samples extracted with 0.01M Tris-HC1 at pH 7.5. Further work on the use of different solvents, surfactants and detergents to optimize the extraction of alkaline phosphatase and gamma-glutamyl transpeptidase were iii conducted. The results obtained showed that 0.01M Tris-HC1 buffer at pH 7.5 alone is sufficient to extract these membrane bound enzymes. Acute studies were conducted by feeding mice with 2-20% of LDS0 of NNitrosodimethylamine (NDMA) and N-Nitrosodiethylamine (NDEA) and mice were killed at 24th, 36', 4gth, 60' and 72"* hours and the liver ALP and GGT were assayed for their activities. Mice fed with 5mg of NDMAlkg of body weight dose for 36 hours showed highest and significant (p<0.05) activation of liver ALP and GGT compared to respective controls suggesting that feeding of NDMA had activated liver marker enzymes activities. The enzyme activities of ALP and GGT for treated mice were 4.215 IUIg protein and 0.656 IUIg protein respectively and in the control liver ALP activity were 1.084 IUIg protein and GGT activity were 0.375 W/g protein. Chronic toxicity study was conducted with oral feeding of 5mg NDMAkg of body weight on weekly basis for 20 weeks. The control and treated mice were sacrificed every fortnight. The severity of neoplasia was studied by histological evaluations and the activity of ALP, GGT, GST and UDPGT were assayed. Studies on these enzymes show significant elevation at (p<0.05) for ALP, GGT and GST compared to respective controls. UDPGT does not show any changes in control and treated mice. ALP and GST was significantly (p<0.05) elevated compared to control at 2"*, 16& and 20' week and GGT was significantly higher than control at week 8", loh, 1 6 a~nd 2 0 ~ T. he highest enzymes activities PERPUsTAKAAN SULTAN ABOUL SAMAD UlllVWSlTl PUTRA MALAYSIA measured for the three enzymes were on the 20' week of experiment. The activities of liver enzyme in treated mice were 5.63 IUIg protein, 1.55 IUlg protein and 2.55 pnole/min/mg protein respectively for ALP, GGT and GST and the activities in control mice during the same week was 1.27 IUIg protein for ALP, 0.376 IUIg protein for GGT and 1.39 j~molelminlmg protein for GST. Histological evaluations through Hematoxilin and Eosin (H&E) staining and Transmission Electron Microscopy (TEM) obtained showed chronic ingestion had caused loss of normal cell organization in liver. Observation with H&E staining and TEM also showed the shrinking of nucleus, cellular and vacuolar degeneration and paler hepatocytes. From 10' week onwards significant @<0.05) increase in lesion score in liver compare to control liver was observed in slides stained with H&E. The present result suggests even at low dose and at weekly feeding to mice, NDMA is capable in elevating turnour marker enzymes in liver and this compound also caused disruption to the normal cell organization of the liver.